Intestinal Lymphangiectasia: A Rare Etiology of Gastrointestinal Bleeding - Mohamed A. Baghi; Abdulwahab Hamid; Ahmed Mohamed Badi; Muneera Jassim Al‐Mohannadi (Clinical Case Reports)
ABSTRACT Intestinal lymphangiectasia (IL) is a rare condition characterized by the blockage of lymphatic fluid draining from the small intestine. It commonly presents with symptoms such as malabsorption, diarrhea, and hypoproteinemia. Bleeding from IL is an infrequent manifestation. We report a rare case of bleeding intestinal lymphangiectasia in a patient who presented with symptomatic anemia and melena. Enteroscopy identified a focal mucosal lesion without active bleeding, while video capsule endoscopy revealed a mucosal lesion with active blood oozing in the proximal jejunum. Subsequent biopsy results confirmed focal lymphangiectasia with vascular congestion. The patient underwent laparoscopic resection of the jejunal lesion. Follow‐up evaluations at 3 and 6 months showed no recurrence of symptoms.